Nitrogen-doped porous carbon material derived from metal–organic gel for small biomolecular sensing. Issue 42 (10th May 2017) - Shih, Yung-Han; Chen, Jian-Hong; Lin, Yaling; Chen, Hsin-Tsung; Lin, Chia-Her; Huang, Hsi-Ya
Abstract : A template strategy for fabricating N-doped porous carbon derived from MOG is demonstrated as a matrix for sensing small biomolecules. Abstract : A simple preparation method of N-doped PCM via direct carbonization of nitrogen containing metal–organic gel was demonstrated. The resultant N-PCM, with high surface area, mesoporosity, and high UV absorption ability, was used as a matrix to assist small-biomolecule sensing in laser desorption/ionization mass spectrometry.